Inequality and fiscal redistribution in Mexico: 1992-2015 - John Scott; Enrique de la Rosa; Rodrigo Aranda Balcazar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper uses income and expenditure surveys from 1992 to 2014 and public tax and spending accounts to estimate the redistributive impact of Mexico's fiscal system over this period. It presents standard and marginal benefit incidence analysis for the principal public transfers (education, health, social security, direct cash transfers) in 1992-2014, and for the full fiscal system for 2008-14. The paper also estimates the effects of a major recent fiscal reform for the years 2015-18: the transition from large subsidies to taxes on petrol. The analysis shows a continuous improvement in the redistributive effects of the fiscal system through the 1990s and 2000s associated with an increase in social spending and in the progressivity of this spending over this period. This trend stagnated and reversed after 2008/2010, reflecting in part an interruption of the expansive and progressive trend of social transfers, but especially a sharp decline of net indirect subsidies.
Keywords: D31; H22; H42; I38; 330; fiscal incidence; taxation; social spending; inequality; poverty; Mexico